Evaluation of Ambient Air Quality at Integrated Waste Processing Facilities and Its Implications for Workers - Eka Fitriani Ahmad; Yoki Yulizar; Muhammad Islam Nasution; Fitra Nurahim; Zaid Karim; Ridho Fauzan; Indriyani Rachman; Julinton Sianturi (Universitas Trisakti, 2026)
Aim: This study evaluated air quality, worker exposure, and health risks at a 3R Integrated Waste Processing Facility in Banyumas Regency, Indonesia, where waste is combusted for extended periods. Methodology and results: Over five consecutive days, concentrations of PM2.5, PM10, CO2, CO, and respirable dust were measured during morning and afternoon shifts. Results revealed persistently hazardous particulate matter levels: PM2.5 exceeded World Health Organization (WHO) limits by 10–90 times, and PM10 by 5–44 times, with no significant difference between sampling periods (p > 0.05). Respirable dust and CO remained within safe thresholds, while CO2 was consistently elevated during morning startup operations. Risk Quotient (RQ) analysis identified CO2 as the only pollutant above the safety threshold (RQ = 1.184), correlating with worker-reported symptoms such as dizziness, fatigue, and difficulty concentrating. Intake calculations confirmed high chronic health risks, particularly for respiratory and cardiovascular disease. Conclusion, Significance, and Impact: Immediate interventions are required, including improved combustion efficiency, local exhaust ventilation, strict use of personal protective equipment, and regular worker health monitoring. Long-term strategies should focus on regulatory reform, advanced emission control technologies, and transitioning toward sustainable waste management through recycling, composting, and circular economy practices. These actions align with United Nations Sustainable Development Goals for health, sustainable cities, and climate action.